Analysing the UPI payments in India and exploring its intersection with sustainable finance - Adnan, Mohd (2024)
This dissertation investigates the intersection of the Unified Payments Interface (UPI) with sustainable finance. The study talks about the adoption and evolution of the UPI payments in India, and how it impacts the financial inclusion in India especially for women. Through qualitative study, including in-depth interviews with women across various demographic, the thesis determines the impact of UPI on financial inclusion, its role in promoting empowerment and its contribution towards achieving the sustainable development goals (SDGs) for India by 2030. Key findings reveal that UPI has indeed enhanced financial inclusion for women and empowered them by increasing their involvement in household financing decisions and by improving their financial literacy. The study also highlights the contribution towards various SDGs. The thesis concludes that other nations can take inspiration from India’s UPI to enhance financial inclusion and sustainability in their countries.